Time-Specific Pattern of Iron Deposition in Different Regions in Parkinson's Disease Measured by Quantitative Susceptibility Mapping - Fu, Xiaodi; Deng, Wenbin; Cui, Xiangqin; Zhou, Xiao; Song, Weizheng; Pan, Mengqiu; Chi, Xiao; Xu, Jinghui; Jiang, Ying; Wang, Qun; Xu, Yunqi (Frontiers in Neurology, 2021)
Studies have shown that spatial specificity of cranial iron deposition in different regions in Parkinson’s disease (PD). However, the time-specific patterns of iron deposition are not yet clear. The purpose of this study was to investigate the time pattern of iron variations and its clinical relevance in multiple grey matter nuclei in PD using Quantitative Susceptibility Mapping (QSM). 30 controls and 33 PD patients were enrolled, including 11 cases of early-stage of PD (ESP) and 22 cases of advanced-stage of PD (ASP) according to the Hoehn-Yahr stages. The iron content in the subcortical nuclei covering substantia nigra (SN), red nucleus (RN), head of the caudate nucleus (CN), globus pallidus (GP), and putamen (PT) was measured using QSM and the clinical symptoms of PD were evaluated by various rating scales. The QSM values in SN, RN, GP and PT significantly increased in PD patients compared with the controls. Further subgroups comparison with the controls indicated the iron content in SN and GP (paleostriatum) gradually elevated in the whole disease duration and was related to clinical features. While the iron content in RN and PT (neostriatum) only elevated significantly in ESP patients, and further iron deposition was not obvious in ASP patients. This study confirmed the time-specific pattern of iron deposition in different brain regions, suggesting that the iron measurement by QSM in neostriatum might be an imaging marker for early diagnosis of PD, while iron deposition in paleostriatum and SN may be used to reveal the disease progression.